Penerapan Akuntansi Pada Usaha Mikro Kecil Menengah (UMKM) Di Kecamatan Montong Gading - Lia Depita Sari; Ida Ayu Nursanty; Rusli Amrul (Akuntabel: Jurnal Ilmiah Akuntansi, 2024)
This study aims to determine the application of accounting in Small, Micro and Medium Enterprises (MSMEs) and explain the constraints of business actors in applying to accounting in Montong Gading District. This research is a descriptive research with a quantitative approach where data collection is done through questionnaires and interviews. The object of this research is Small and Medium Enterprises (MSMEs) actors located in Montong Gading District. A total of 75 data were successfully collected using the sampling method with purposive sampling technique. The results of this study illustrate that 80% of MSMEs business actors in Montong Gading District do not know accounting and financial reports in accordance with SAK EMKM, while 20% of MSMEs business actors already know. As for the application of accounting in accordance with SAK EMKM, as much as 92% have not implemented it and only 8% have implemented accounting in accordance with SAK EMKM. The obstacle faced by MSMEs is that they think accounting and making reports is difficult and they don't know what to do. The next obstacle faced by MSMEs actors is a minimal understanding of Accounting and SAK EMKM, this is due to a lack of socialization or training from the Government or authorized institutions.